Co-movements between public and private wages in the EU: What factors and with what policy implications? - Benedicta Marzinotto; Alessandro Turrini (IZA Journal of European Labor Studies, 2017)
This paper assesses the relationship between public and private wages in the EU, as measured by general government and manufacturing compensations, respectively. We find that the long-run relation between the two is stronger when the government is a large employer. Manufacturing compensations are better aligned with productivity and unemployment when general government compensations, to which they generally respond, are set through bargaining. Finally, manufacturing compensations react in the same way whether those in the general government sector are increased or cut, a relation that seems to hold also under fiscal consolidation provided the government is a large employer.
Keywords: C32; E24; E62; H59; 330; General government compensations; Wage setting; Cost competitiveness; Fiscal consolidation; Co-integration